Análisis y exposición de los modelos virtuales : los modelos de las bibliotecas nacionales. - Herrera Morillas, José Luís (Revista General de Información y Documentación, 2002)
The present study analyses and evaluates 135 virtual exhibitions; on the basis of this study a method, including 15 indicators applied in direct observation of each exhibition on Internet, is proposed for the analysis of this type of web.